Effect of Vitamin E (α-tocopherol) and Different Temperatures on Cooled Porcine Semen Viability - Labêta, Camilla Pereira de Souza; de Mello, Marco Roberto Bourg; Silenciato, Lara Nogueira; Arrais, Aline Matos; de Vasconcelos, Bruno da Silva (Brazilian Journal of Veterinary Medicine, 2018)
The objective of this study was to evaluate the addition of α-Tocopherol to swine insemination doses stored at 5 and 15°C for a period of 72 hours. Semen samples (n=9) collected from three adult Pietrain boars were treated with or without 200 μg/mL of α-Tocopherol. The treatments were: T1: α-Tocopherol + cooling to 5°C; T2: α-Tocopherol + cooling to 15°C; T3: no α-Tocopherol + cooling to 5°C; T4: no α-Tocopherol + cooling to 15°C. All samples were evaluated up to 72 hours for sperm motility and intensity of movements every 12 hours, and the hiposmotic test was performed every 24 hours. The average of the motility, the intensity of movements and hiposmotic test (HOST) were analyzed by chi-square test (х²) with 5% significance level. There was a significant difference (p <0.05) for motility when comparing the temperatures of 5 and 15°C regardless of α-Tocopherol during the period between 12 and 72 hours. The highest motility values were obtained at 15°C. It was also observed a difference (p <0.05) for sperm motility between temperatures of 5 to 15°C when compared only the samples with α-Tocopherol, as well as the samples without this substance. The higher motility was obtained with 15ºC. No difference was observed for the intensity of movements and membrane integrity between samples added or not of α-Tocopherol, in any of the temperatures and times evaluated. We concluded that the temperature of 15°C was more efficient for boar semen preservation over 72 hours. It is also concluded that the addition of 200μg/mL of α-Tocopherol showed no improvement in the viability of cooled porcine semen